Wireless power transfer system with domino structure - Ganeshkumar Mahalingam (Nanyang Technological University, 2022)
The communication of electrical sources by electromagnetic waves is known as wireless transmission technology. Transmission paths are not bounded by just physical cables, making energy transmission more flexible and very practical for various situations. This study examines the transmission theory for magnetic resonant induction system and eventually create a wireless power transfer system with this technology.